Stepper motor control / Nur Ilyana Abdullah Sani and Noor Hidayati Ishak - Abdullah Sani, Nur Ilyana; Ishak, Noor Hidayati (2004)
The stepper motor control circuit is a simple, low-cost hardwired step per motor control circuit that can be used in low- power application. This circuit consist of component IC 555 timer astable multivibrator, IC 7474 dual 'D' flip-flop as ring counter, ULN 2003 IC consist of Darlington transistor array, resistor, capacitor, diode and stepper motor. The type of stepper motor is variable reluctance. It has four w inding and need 12 volt power supply to moving the stepper motor. This circuit is operating and moving the stepper motor when the 5 volt is apply to the input circuit and 12 \olt is apply to stepper motor By pressing the reset switch, the stepper motor can stop moving. On releasing the reset switch, the stepper motor again starts moving in the same direction. Application of the stepper motor control circuit that is using in moving toys such as car control. The total budget to make hardware this circuit is RM 43.75.